Infusing creativity in teaching and learning: an Islamic approach - Sulaiman, Kabuye Uthman (2014)
Infusion of creativity in teaching and learning is a key element in the development of any nation. It is a problem-solving technique where students learn to think “out of the box”; they learn to ‘create’ (generate new ideas, or ways of viewing things, designing, constructing, planning, producing, inventing) which is the highest level of Bloom’s Taxonomy. Many Muslim scholars are of the opinion that the regress of the Islamic world was due to intellectual decline; that is, taqlid (following others and holding uncritical faith in their opinions) and jumud al-Fikr (stagnation of the mind). Therefore, the revival of Islamic civilization requires liberation of the Muslim mind from all forms of mental slavery. This paper deals with infusion of creativity in teaching and learning as a way forward for Muslims. Its objectives are twofold; firstly, to analyze the importance and significance of infusion of creativity in teaching and learning on the basis of Qur’an and Sunnah; and secondly, to highlight the objective of creativity in education from an Islamic perspective; that is, rejection of taqlid. To achieve these objectives, the paper begins with explanation of the conceptual meanings of creativity and its development in Islamic thought and heritage. It concludes with recommendations for creative teaching. Keywords: Creativity, teaching, learning, taqlid, jumud al-Fikr, education, Islamic Thought and